2007
DOI: 10.1051/0004-6361:20077939
|View full text |Cite
|
Sign up to set email alerts
|

The habitability of super-Earths in Gliese 581

Abstract: Aims. The planetary system around the M star Gliese 581 consists of a hot Neptune (Gl 581b) and two super-Earths (Gl 581c and Gl 581d). The habitability of this system with respect to the super-Earths is investigated following a concept that studies the long-term possibility of photosynthetic biomass production on a dynamically active planet. Methods. A thermal evolution model for a super-Earth is used to calculate the sources and sinks of atmospheric carbon dioxide. The habitable zone is determined by the lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…One of them, Gl 581, is hosting two planets that potentially fall into the star's habitable zone (von Bloh et al 2007;Selsis et al 2007). Recently, Tarter et al (2007) has concluded that M dwarfs should be included in the quest for habitable worlds and evidence of life, because they are so numerous and there are no obvious reasons why activity should destroy life on them.…”
Section: Introductionmentioning
confidence: 99%
“…One of them, Gl 581, is hosting two planets that potentially fall into the star's habitable zone (von Bloh et al 2007;Selsis et al 2007). Recently, Tarter et al (2007) has concluded that M dwarfs should be included in the quest for habitable worlds and evidence of life, because they are so numerous and there are no obvious reasons why activity should destroy life on them.…”
Section: Introductionmentioning
confidence: 99%
“…The habitability of Gl 581c and d has been investigated by Selsis et al (2007) and von Bloh et al (2007a), based on the discovery data published by Udry et al (2007). In their study, von Bloh et al (2007a) applied a box-model of the Earth, which incorporates the carbonate-silicate cycle, requiring a A&A 522, A23 (2010) Johnson & Wright (1983), Lacy (1977) surface reservoir of liquid water and a tectonically active planet.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, von Bloh et al (2007a) applied a box-model of the Earth, which incorporates the carbonate-silicate cycle, requiring a A&A 522, A23 (2010) Johnson & Wright (1983), Lacy (1977) surface reservoir of liquid water and a tectonically active planet. It includes the exchange of CO 2 between the mantle and crust of the planet and its atmosphere by assuming parameterizations for continental growth and spreading rate.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to consider atmospheres similar to Earth, Venus or Mars (or their atmospheres in earlier epochs). Considering the amount of greenhouse gases including CO 2 , Selsis et al (2007) and von Bloh et al (2007) both found that Gl 581d is more likely to be habitable (that is with surface temperatures consistent with liquid water) than Gl 581c. Other investigators consider atmospheres that radically depart from the terrestrial planets in our solar system.…”
Section: Super Earth Atmospheresmentioning
confidence: 99%